In silico characterization of WRKY33 TF from Sinapis alba - JANGID, VINOD KUMAR; DIXIT, SHIKHA; TIWARI, LALIT DEV; SINGH, INDRA; RAO, ATMAKURI RAMAKRISHNA; GROVER, ANITA (The Indian Journal of Agricultural Sciences, 2020)
The WRKY family of transcription factors modulates the host defense mechanisms in response to various environmental stresses. The role of WRKY33 in plant defense and its crosstalk with defense hormone was well established in Arabidopsis but very few information was noted in Sinapis alba. The present study was carried out in 2017, in which computational approaches to characterize the structural and functional features of SaWRKY33 transcription factor was used. Full length WRKY33 coding sequence (1509 bp) from S. alba has been cloned, sequenced and identified as AtWRKY33 homolog. The expression of SaWRKY33 was scored higher in fungal pathogen challenged and jasmonate-treated samples while lower expression was noticed in salicylate-treated samples. Phylogenetic classification, sequence alignment and MEME-based motif scanning demonstrated the remarkable sequential conservation in the WRKY domains and SaWRKY33 clusters with Crambe abyssinica exhibiting the monophyletic origin and paraphyletic evolution from their wild relatives. STRING data showed SaWRKY33 were interacted with MKS1, MPK3, SIB1, and those are involved in plant defense responses against diverse stress conditions. The homology-based modeling of SaWRKY33 functional WRKY domains showed acceptable Ramachandran statistics and satisfies all the necessary energy parameters. The Hex Docking server-based analysis of DNA-protein interaction showed that WRKY domain binds to the W-box through WRKYGQK along with few conserved amino acid residues in the flanking sequences and zinc finger motifs.